Characterization and Photocatalytic Activity of TiO2(rod)-SiO2-Polyaniline Nanocomposite - Sri Wahyuni; Eko Sri Kunarti; Respati Tri Swasono; Indriana Kartini (Universitas Gadjah Mada, 2018)
A study of TiO2(rod)-SiO2 composites coated with polyaniline (PANI) has been performed. PANI was synthesized through in-situ polymerization of aniline at various concentration (0.0137, 0.0274, and 0.0411 M) on the composite under acidic condition. PANI was confirmed by the appearance of C=N, C=C vibrations and the redshift of the band-gap from 3.14 eV for the TiO2(rod)-SiO2 into 3.0 eV for the TSP01 composite. It is also shown that the polymerization does not change the crystal structure of TiO2(rod)-SiO2 as confirmed by the XRD pattern. The TEM image shows a mixed structure of SiO2 coated by TiO2(rod)-PANI layers and the oxides coated by PANI layers. Therefore, the surface area of the resulted TiO2(rod) and the composites did not change significantly. The T TiO2(rod)-SiO2-PANI composite give small improvement under visible irradiation from 20.25 to 25.59% (around 5% from the bulk of TiO2(rod)) and from 25.03 to 25.59% (around 2% from TiO2(rod)-SiO2 composite). The mixed structure of the composites, as well as the formation of excessive layers of PANI, are possibly the case for the low photoactivity. Further improvement to obtain a core-shell structure with a thin layer of PANI is still sought.